Plasma IGFBP-2 levels reveal heterogeneity in hepatic fat content in adults with excess visceral adiposity - Rauzier, Chloé; Chartrand, Dominic J.; Alméras, Natalie; Lemieux, Isabelle; Larose, Eric; Mathieu, Patrick; Pibarot, Philippe; Lamarche, Benoît; Rhéaume, Caroline; Poirier, Paul; Després, Jean-Pierre; Picard, Frédéric (Frontiers in Endocrinology, 2023)
Aim/hypothesis: Although excess visceral adiposity (VAT) is generally associated with increased liver fat (LF), recent evidence has revealed heterogeneity in LF content among adults with visceral obesity, potentially contributing to specific differences in cardiometabolic outcomes. Reasons for such discordant VAT-LF phenotypes are largely unknown. The present study aimed at assessing whether circulating levels of insulin growth-factor binding protein-2 (IGFBP-2) could be a useful biomarker in the identification of heterogenous and discordant VAT-LF phenotypes. Methods: A sample of 308 middle-aged Caucasian apparently healthy men and women without cardiovascular symptoms were studied for the present cross-sectional analyses. Fasting plasma glucose and lipid levels were assessed and an oral glucose tolerance test was performed. Hepatic fat fraction (HFF) was measured using magnetic resonance spectroscopy whereas VAT was assessed by magnetic resonance imaging. Plasma IGFBP-2 levels were quantified by ELISA. Participants were then classified on the basis of median VAT (81 mL) and IGFBP-2 levels (233 ng/mL). Results: Individuals with high levels of VAT were characterized by higher waist circumference, lower insulin sensitivity, as well as by higher plasma triglyceride and lower HDL-cholesterol levels. Plasma IGFBP-2 levels were inversely correlated with HFF (r = -0.39, p < 0.0001). Among men and women with high levels of VAT, those with low levels of IGFBP-2 had significantly higher HFF (7.5 ± 0.7%), compared to participants with high IGFBP-2 concentrations (3.2 ± 0.5%, p < 0.0001). Conclusions: In the presence of excess VAT, high IGFBP-2 concentrations are associated with low levels of LF. Although additional studies will be necessary to establish causality and further clarify the clinical implications of these observations, these findings are concordant with a novel function of IGFBP-2 in modulating susceptibility to non-alcoholic fatty liver disease (NAFLD) in the presence of visceral obesity.